The Influence of Risk Perception, Personal Data Protection, and Digital Service Quality on Customer Trust in Digital Banking Services in Indonesia - Widya Rahayu; Helviana Hasibuan; Yuni Franciska Br Tarigan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The digital transformation in Indonesia’s banking sector has significantly increased the use of digital banking services; however, it has not been fully accompanied by optimal customer trust. This study aims to examine the effect of perceived risk, data privacy protection, and digital service quality on customer trust, both partially and simultaneously. A quantitative approach was employed using survey data collected from 150 digital banking users in Indonesia. Data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that perceived risk has a negative and significant effect on trust, while data privacy protection and digital service quality have positive and significant effects on trust. Simultaneously, all variables significantly influence trust, with an R² value of 0.672, indicating strong explanatory power. Compared to prior studies, this research contributes novelty by integrating these three variables into a comprehensive model. The findings reveal that digital service quality is the most dominant factor influencing customer trust. This study concludes that enhancing customer trust requires an integrated approach through effective risk management, strengthened data protection, and continuous improvement in digital service quality.